Coleman Principles and Krasnosel'skii Genus in Eigenfunction Problems - Suvorov, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider a simple semilinear elliptic eigenfunction problem. Using it as an example, we demonstrate functional topological methods that give information on the critical numbers almost as detailed (in the qualitative sense) as in the case of separation of variables in an analogous linear problem.